THE EFFECTIVENESS OF TEACHING READING ACHIEVEMENT BY USING VOCABULARY SELF-COLLECTION STRATEGY TECHNIQUE AT THE SEVENTH GRADE STUDENTS OF MTsN 1 KEDIRI - yunitasari, putri (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 1 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Reading comprehension at Junior High School is difficult, because reading contains not only vocabulary but also grammar, so the students must undestand both of them. They feel bored when learn English because they think English is hard to learn.This study aims at knowing how the vocabulary self-collection strategy (VSS) affects the reading achievement for the sseventh grade students at MTsN 1 Kediri.The research design selected was Posttest-Only Control-Group Design. This research used two classes which were randomly chosen; they were control group and experimental group. The result shows that experimental group’s achievement is higher than the control one.Vocabulary Self-Collection Strategyis effective to be used in language teaching specifically in teaching reading achievement.